상급종합병원 응급실에서 진료 후 예약된 외래의 예약 부도에 영향을 미치는 요인 - 유춘섭; Choon Seop Yoo; 김태현; Tae Hyun Kim; 이상규; Sang Gyu Lee; 장석용; Suk-yong Jang (HIRA Research, 2025)
Background: Outpatient appointments scheduled through the emergency department (ED) differ from routine appointments made via follow-ups or self-scheduling systems, as they are arranged at discharge following emergency care. Despite their importance in ensuring continuity of care, ED-scheduled appointments often face higher no-show rates. This study aimed to analyze the no-show rate and identify the key factors influencing appointment adherence among patients discharged from the ED. Methods: A retrospective analysis was conducted on outpatient appointments scheduled through the ED of a tertiary hospital in Seoul, Korea, between January 1 and December 31, 2019. Of the 21,634 ED-scheduled appointments, 10,751 were included from six alternating months. Sociodemographic, appointment-related, and clinical characteristics were analyzed. Multivariate logistic regression was used to determine significant predictors of no-show behavior. Results: The overall adherence rate for ED-scheduled outpatient appointments was 43.6%, with a no-show rate of 56.4%, which was substantially higher than that for general outpatient appointments. Significant factors associated with no-shows included alcohol use, lower patient acuity based on the Korean triage and acuity scale (KTAS), and appointments arranged by emergency medicine physicians. Conversely, patients who underwent complex procedures such as suturing or minor surgeries demonstrated better adherence. Waiting time was also a critical factor, with no-show rates exceeding 80% when the waiting period was longer than two weeks. Conclusion: This study highlights the need for targeted interventions to reduce the no-show rates in ED-scheduled outpatient appointments. Tailored strategies based on patient characteristics and appointment conditions are essential for improving scheduling efficiency and continuity of care. Further research across diverse healthcare settings is recommended to validate these findings and inform broader policy developments.